Effects of Environmental Exposures on Fetal and Childhood Growth Trajectories - Tongzhang Zheng; Jie Zhang; Kathryn Sommer; Bryan A. Bassig; Xichi Zhang; Jospeh Braun; Shuangqing Xu; Peter Boyle; Bin Zhang; Kunchong Shi; Stephen Buka; Siming Liu; et al. (Annals of Global Health, 2016)
Delayed fetal growth and adverse birth outcomes are some of the greatest public health threats to this generation of children worldwide because these conditions are major determinants of mortality, morbidity, and disability in infancy and childhood and are also associated with diseases in adult life. A number of studies have investigated the impacts of a range of environmental conditions during pregnancy (including air pollution, endocrine disruptors, persistent organic pollutants, heavy metals) on fetal and child development. The results, while provocative, have been largely inconsistent. This review summarizes up to date epidemiologic studies linking major environmental pollutants to fetal and child development and suggested future directions for further investigation.